2017
DOI: 10.1111/nmo.13155
|View full text |Cite
|
Sign up to set email alerts
|

Resilience is decreased in irritable bowel syndrome and associated with symptoms and cortisol response

Abstract: Background: Irritable bowel syndrome (IBS) is a stress-sensitive disorder associated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 34 publications
3
43
0
Order By: Relevance
“…All subjects completed a BRS questionnaire (Park et al, 2018). The BRS consists of six questions and is used to characterize the ability of an individual to recover from stressful events (Smith et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…All subjects completed a BRS questionnaire (Park et al, 2018). The BRS consists of six questions and is used to characterize the ability of an individual to recover from stressful events (Smith et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…In all cases, however, it is likely that the “three-hit concept” of vulnerability and resilience persists: a genetic predisposition and early life adverse events are necessary so that a later-in-life stressor can exhibit negative health outcomes, and one or more missing may result in higher resilience 65 . It is of importance to note that resilience has not yet been thoroughly investigated in relation to GI functions in animals (and humans) under stress; it is, however, known that patients with IBS lack resilience, and low resilience was associated with worse IBS severity, lower quality of life, more early life stressful events, and stress hyper-responsiveness 66 . Similarly, in patients with IBD, the role of (maladaptive) coping is only beginning to be unraveled (for example, 67 69 ), calling for translational research on individual risk and resilience in patients with GI conditions.…”
Section: Current Animal Stress Research In the Gastrointestinal Tractmentioning
confidence: 99%
“…However, the evidence for gut microbial alterations in IBS is currently limited [ 8 , 9 , 10 ]. Alterations in psychobiological stress reactivity are also clearly implicated in IBS [ 11 , 12 , 13 ]. Data from our own and other research groups have shown associations between psychological stress and microbial factors [ 14 , 15 , 16 ], and animal models suggest a connection between stress-induced shifts in gut microbiota, visceral pain and altered brain-gut communication [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%